FACTORS RESTRICTING RURAL CREDIT FOR FAMILY FARMING FROM THE PERSPECTIVE OF CREDIT ANALYSTS AT THE SICOOB CENTRO COOPERATIVE - da Silva, Wendel Saymon Batista (Seven Editora, 2026)
Family farming is one of the most outstanding activities in Brazilian agribusiness. In addition to productive contributions, family producers, among other economic and social contributions, collaborate especially in income distribution andmaintenance of men in the countryside. However, family farmers face challenges in developing their activities, such as the restriction on obtaining rural credit. With this, the present study sought to analyze the factors that restrict rural credit for family producers in the credit cooperative Sicoob Centro, in the city of Ji-Paraná in the state of Rondônia. In addition, the study also endeavored to analyze the profile of family producers who take out rural credit, survey the main lines of credit used by rural family producers and investigate with Sicoob Centro credit analysts the actions that can minimize credit restrictions. For that, descriptive research with a quantitative approach was used through the deductive method. As for data collection, bibliofigureical research, documentary research and field research were used, using a questionnaire with open questions, with 13 responses being collected from credit analysts at Sicoob Centro. As a result, it was noticed that the majority (14.52%) of family producers who take credit from the cooperative are aged between 44 and 48 years old; 67.16% of family farmers work in beef cattle; and 91% of the credits taken are in the PRONAF Costing and Pre-Custing modality. In addition, it was also found that, according to the interviewees, the main factors restricting rural credit for family farmers are the high indebtedness of producers, lack of information about the borrower, delay in granting credit and the lack of of guarantees.